Radiological anatomy analysis of uncinate process, concha bullosa, and deviated septum in chronic rhinosinusitis - Retno Sulistyo Wardani; Arroyan Wardhana; Endang Mangunkusumo; Vally Wulani; Brent Anthony Senior (Oto Rhino Laryngologica Indonesiana, 2017)
Background: Risk factors of chronic rhinosinusitis include epithelial disease related to disturbanceof mucociliary transport system, anatomical variations obstructing the ostiomeatal complex anddysfunction of neural regulation.Purpose: To find the prevalence of deviated septum, concha bullosa andlateral deflection of the uncinate process in ipsilateral chronic rhinosinusitis.Methods: A retrospectivestudy of computed tomographic (CT) scans of chronic rhinosinusitis patients who were not cured by6 weeks of maximal medical treatment of rhinosinusitis. Pneumatization of the middle turbinate anddeviation of the septum were evaluated on coronal slices, while lateral deflection of the uncinate processwas also assessed by calculating the angle using Osirix software (Pixmeo, Geneva, Switzerland).Results:One hundred ninety-three CT scans comprising 386 nasal sides were analyzed. The prevalence of thecombination of deviated septum, concha bullosa and lateral deflection of the uncinate process occurringconcurrently with ipsilateral maxillary sinusitis was found to be 32,9% (p=0.01, OR=9.1, 95% CI=1.2-69.7). The prevalence of deviated septum with concha bullosa was found in 40.9% with ipsilateral maxillarysinusitis (p=0.03, OR=3.8, 95% CI=1.1-13.3). One single anatomical variation of lateral deflection ofthe uncinate process had a proportion of 71.5% in ipsilateral maxillary sinusitis (p=0.03, OR=2.7 95%CI=1.1-6.9).Conclusion: Deviated septum, concha bullosa and lateral deflection of the uncinate processwere frequently present in the existence of ipsilateral chronic maxillary rhinosinusitis. It suggested greaterassociation compared to one or a combination of two anatomical variation in the role of local factorscontributing to sinonasal epithelial dysfunction.Keywords: chronic rhinosinusitis, deviated septum, concha bullosa, lateral deflection of uncinate process ABSTRAKLatar belakang: Rinosinusitis kronis adalah penyakit inflamasi yang mengakibatkan gangguankeseimbangan homeostasis fungsi hidung dan sinus paranasal. Patofisiologinya terjadi melalui kombinasigangguan transpor sistim mukosiliar, variasi anatomi yang menyempitkan kompleks ostiomeatal sertagangguan regulasi persarafan sensorik, simpatis dan parasimpatis. Tujuan: Untuk mengidentifikasiprevalensi septum deviasi, konka bulosa dan prosesus unsinatus defleksi lateral, serta hubungannya denganrinosinusitis kronik yang terjadi pada sisi yang sama (ipsilateral). Metode: Penelitian retrospektif potonglintang pada tomografi komputer (TK) pasien dengan rinosinusitis kronik yang tidak sembuh dengan terapimedikamentosa maksimal selama 6 minggu. Pneumatisasi konka media dan deviasi septum dievaluasipada potongan koronal, sedangkan defleksi prosesus unsinatus ke lateral dinilai dan diukur sudutnyadengan menggunakan piranti lunak Osirix (Pixmeo, Geneva, Switzerland). Hasil: Analisis dilakukanpada 193 TK yang terdiri dari 386 sisi hidung. Prevalensi kombinasi septum deviasi, konka bulosa danprosesus unsinatus defleksi lateral yang terjadi bersamaan dengan sinusitis maksila ipsilateral adalah 32,9% (p=0,01, OR=9,1, 95% CI=1,2-69,7). Prevalensi septum deviasi dengan konka bulosa ditemukanpada 40.9% sinusitis maksila ipsilateral (p=0,03, OR=3,8, 95% CI=1,1-13,3). Variasi anatomi tunggalyaitu prosesus unsinatus defleksi lateral memiliki proporsi 71,5% pada sinusitis maksila ipsilateral.(p=0,03, OR=2,7 95% CI=1,1-6,9). Kesimpulan: Septum deviasi, konka bulosa dan prosesus unsinatusdefleksi lateral sering ditemukan bersamaan dengan kejadian sinusitis maksila ipsilateral. Kombinasitiga variasi anatomi yang menyempitkan kompleks ostiomeatal (KOM) lebih kuat daripada hanya satuvariasi anatomi atau kombinasi 2 variasi anatomi, sebagai faktor lokal yang berkontribusi terhadapdisfungsi epitel sinonasal serta gagalnya resolusi inflamasi kronik.Kata kunci: Rinosinusitis kronis, septum deviasi, konka bulosa, prosesus unsinatus defleksi lateral